The Eurosystem collateral framework explained - Ulrich Bindseil; Marco Corsi; Benjamin Sahel; Ad Visser (European Central Bank (ECB), 2017)
The Eurosystem collateral framework (ESCF) has played a key role in the ECB monetary policy implementation since 1999. Moreover, the financial and sovereign debt crisis and with it the increased reliance of banks on central bank credit have underlined the importance of central bank collateral frameworks. Broad collateral frameworks have helped prevent large-scale liquidity-driven defaults of financial institutions in all major advanced economies. More recently, they have allowed central banks to provide a large amount of - at times targeted - longer-term credit. Nevertheless, a number of authors have argued that the ESCF is too forthcoming or broad and that it does not afford the central bank sufficient protection. This paper first explains and justifies the logic of collateral frameworks in general and that of the ESCF in particular. It then reviews the main critical comments. It concludes that the ESCF has been effective (i) in providing an adequate level of elasticity for Eurosystem credit, and (ii) in protecting the Eurosystem from financial losses despite the severity of the financial and sovereign debt crisis and the large amounts of longer-term credit provided by the Eurosystem.
Keywords: E58; 330; Central banking; Collateral; ECB; Eurosystem; Lender of Last Resort; Operations